A practical optimization method for enhancing drilling efficiency in panel furniture manufacture - Guokun Wang; Xianqing Xiong; Sijie Fu; Mei Zhang; Lujie Yang (PLoS ONE, 2026)
Drilling is one of the most complex processes in the manufacturing of panel-type furniture and has a significant impact on both production efficiency and takt-time stability. With the growing demand for large-scale customized furniture, the complexity of drilling operations has increased substantially. Moreover, variations in equipment capabilities further hinder the automation and standardization of this process. In this technical note, we ad-dress three common challenges in the drilling process of panel furniture: the inability to process horizontal holes located on fixed reference edges, low slotting efficiency, and pro-longed idle time of drilling equipment. To resolve these issues, we propose a set of strategies based on flipping, slot extension, and hole-slot logic transformation. The proposed methods have been successfully implemented in a large-scale customized panel furniture production line. Practical results demonstrate their effectiveness in improving drilling efficiency. Specifically, for panel components previously limited by low slotting efficiency, the optimization was applicable to 42.30% of the parts. Additionally, for panels that previously suffered from long idle periods during processing, the drilling efficiency increased by 56.01%. These findings confirm the practical value and applicability of the proposed approach in industrial settings, particularly in enhancing operational consistency and promoting automation in mass-customized furniture manufacturing.